PENGARUH GREEN ACCOUNTING DAN KINERJA KEUANGAN TERHADAP PENGHINDARAN PAJAK PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2018-2022 - Maya Ahyani; Rohma Septiawati; Ade Trisyanto (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The purpose of this study is to find out the impact of green accounting and financial performance on tax avoidance on mining companies listed on the Indonesian Stock Exchange, publish financial reports and registered at the Ministry of Environment and Forestry PROPER for the period 2019 to 2022. A sample of 85 on a mining company. Sampling using purposive sampling techniques. Using quantitative methods, the data is taken as secondary data. Technique in data processing using SmartPLS version 3.0. The research uses stakeholder theory, to help corporate management increase value creation as a result of environmental activities carried out and minimize possible losses to stakeholders. The measurement of green accounting uses the PROPER rating published by the Ministry of Environment and Forestry. Financial performance is projected by Return On Asset (ROA). Measurement of tax deduction using Cash Effective Tax Rate (CETR). The results of this study show that green accounting variables have no significant impact on tax avoidance, while financial performance variables result have a significant effect on tax evasion in mining companies listed on the Indonesian Stock Exchange in 2019 to 2022.